Analisando significados de capas da revista Raça Brasil: um estudo de caso à luz da semiótica social - Viviane Seabra Pinheiro (2007)
In the Brazilian context, the descriptive framework provided by the Grammar of the Visual Design (KRESS & VAN LEEUWEN, 1996) alongside the Systemic-Functional Grammar (HALLIDAY & MATTHIESSEN, 2004) has been increasingly applied as an efficient methodology to a social semiotic approach (BIAVATI e MAGALHÃES, 2003; HEBERLE, 2004; FELIPE, 2006; SANTANA, 2006; among others). This thesis aims at contributing to an interface of these grammars and to the development of this approach in the Brazilian context, by means of analyzing the covers of the 1996, 1998, 2004 and 2006 November editions of the magazine Raça Brasil, a black-audience-oriented publication. Building on analytical tools of these grammars, this research aims mainly at analyzing the representational, interactive and compositional meanings constructed through the visual component, as well as the ideational meaning of the most significant headlines and therelation between these meanings and the concept black consciousness. The meanings constructed by means of the visual and verbal semiotic modes in the editions and/or periods surveyed are compared so as to identify discursive changes. The analysis points at an ambivalent orientation in the magazine Raça Brasil. In this study, this ambivalence arises in several ways. It is possible to observe a movement towards the promotion/strengthening of the readers black consciousness, mainly by means of stimulating their self-esteem. At the same time, representations built in the magazine generally evoke biased discourses, which are assimilated and reproduced. Furthermore, it is possible to observe, alongside a politicized orientation, the existence of a marketing interest presumably determining both the cover layout and the content of some headlines. Finally, the semiotic changes in the covers underanalysis lead to the hypothesis that, on the one hand, the magazine may have been consolidated as a black-audience-oriented publication and, on the other hand, its target public have changed throughout a 10-year temporal cline.